MINERAL CARBONATION AS A POTENTIAL CARBON DIOXIDE STORAGE OPTION FOR THE REGION OF WESTERN MACEDONIA, GREECE - Koukouzas, N.; Ziock, H.; Ziogou, F.; Typou, I. (Bulletin of the Geological Society of Greece, 2007)
The long-term storage of the greenhouse gas C02 generated by fossil fuel-fired power plants in the form of stable mineral carbonates appears to be a promising option for reducing global CO2 emissions. In the case of mineral carbonation captured gaseous CO2 is chemically stored in an exothermic reaction by the carbonation of magnesium or calcium silicate minerals, forming environmentally benign and thermodynamically stable products. The purpose of this paper is to give an overview of the carbon dioxide storage by mineral carbonation and to examine the feasibility of this sequestration option in the region of Western Macedonia. The main candidate minerals for carbonation and their sequestration capacity are presented. Furthermore, the most promising mineral carbonation process routes as well as the thermodynamics and kinetics of carbonation reaction are addressed, based on a review on the published literature. In Greece abundant magnesium-rich ultramafic rocks exist that probably could support the national CO2 emissions abatement policy. The attractiveness stems from the favourable geographical relationship between large stationary CO2 emission sources and potential magnesium silicate deposits. Thus, a roughly description of the olivine deposits and their quality in the region of Western Macedonia will be provided